Sosialisasi Perumahan dan Permukiman Di Pulau Lombok Dalam Perspektif Desa Kota - Hirsan, Fariz Primadi; Susanti, Febrita; Widayanti, Baiq Harly; Sushanti, Ima Rahmawati; Yuniarman, Ardi (Universitas Muhammadiyah Mataram, 2025)
Abstract: Lombok Island faces rapid development with intense rural-urban interaction, causing land-use shifts and housing challenges. Communities in transitional areas often lack understanding of regulations, decent housing standards, and sustainable environmental management. This community engagement initiative aimed to enhance stakeholders' and community understanding of housing and settlement regulations from a rural-urban perspective, increase awareness of sustainable planning, and foster active government-community participation. The method involved a technical guidance participatory meeting at the West Nusa Tenggara Province Housing and Settlement Agency on April 15, 2025. Stages included an initial survey, interactive visual materials, pre-test, lectures, discussions, and a post-test. Evaluation results showed a significant understanding increase from 73.45% to 87.04% regarding rural-urban housing typologies. Critical issues identified were unplanned land conversion, difficulty accessing information/permitting, infrastructure disparities, and evolving housing aspirations. These findings highlight the need for an integrated approach to Lombok's settlement developmentAbstrak: Pulau Lombok mengalami dinamika pembangunan pesat dengan interaksi